Dampak Undang-Undang Nomor 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan Terhadap Ekonomi Indonesia - Muhammad Takhsin; Putri Latiffa Azzahra (Journal of Law and Economics, 2023)
This research aims to evaluate the impact of Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (UU P2SK) on the Indonesian financial sector. By focusing on the effectiveness of the P2SK Law and its role in overcoming economic challenges and encouraging financial inclusion, this research uses a holistic approach with descriptive analysis, econometrics and case studies. The P2SK Law brings significant changes in the regulation and structure of the financial sector, especially in digital financial services and consumer protection. Econometric analysis shows increasing investor confidence, while financial sector innovation and financial access require further monitoring. A case study in Aceh Province highlights the positive impact of the P2SK Law, but factors such as infrastructure and financial literacy influence its implementation. Policy recommendations include improving infrastructure and increasing financial literacy to increase the impact of the P2SK Law. The results can provide insight for policy makers and financial practitioners to push Indonesia's financial sector towards greater inclusiveness and sustainability